Analisis Pemanfaatan Teknologi dalam Pembelajaran untuk Anak Usia Dini - Ihtiari Prastyaningrum; Pramudya Ardi; Filipus Yubelleo Dari Pratama (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Education for early childhood has undergone many changes. Challenges Technological developments require educators to be more creative in packaging learning models for students. During the era of the covid pandemic the learning process took place online. Now the pandemic is over and teaching and learning activities have returned to normal. This is a challenge for teachers, because teachers must be able to convey learning material more creatively. Combining technological developments with the needs of students at school. This study aims to determine the extent to which the use of technology in early childhood learning. The methods used included questionnaires, interviews and observations, by taking a sample of 26 schools in the Madiun City area. The results of the study show that all schools have utilized technology, but so far its use has been limited to learning media, such as the use of laptops, projectors, internet or OHPs. Technology has not been used directly in learning resources such as being used in educational games.